Effect of Torulaspora delbrueckii Yeast on the Anthocyanin and Flavanol Concentrations of Cabernet franc and Pinotage Wines - Minnaar, P.P.; Ntushelo, N.; Ngqumba, Z.; van Breda, V.; Jolly, N.P. (South African Journal of Enology and Viticulture, 2016)
Pinotage and Cabernet franc grape must were inoculated with Saccharomyces cerevisiae and Torulaspora delbrueckii yeasts. Differences in colour were observed between Pinotage (S. cerevisiae) and Pinotage (T. delbrueckii) wines, whereas differences in berry and herbaceous character were observed between Cabernet franc (S. cerevisiae) and Cabernet franc (T. delbrueckii) wines. Mouthfeel properties between treatments for both wines were not significantly different. Overall quality was slightly higher in wines inoculated with T. delbrueckii compared to wines inoculated with S. cerevisiae. Anthocyanins and flavanols measured in Pinotage wines made with T. delbrueckii were higher compared to Pinotage must inoculated with S. cerevisiae. Cabernet franc wines made with S. cerevisiae were higher in anthocyanin glycoside and flavanol concentrations compared to Cabernet franc wines made with T. delbrueckii. Insignificant differences in acetylated and coumarylated anthocyanins were evident between Cabernet franc (S. cerevisiae) and Cabernet franc (T. delbrueckii) wines. Principal component analysis showed that epigallocatechin gallate, epicatechin gallate, procyanidin B2, peonidin 3-O-glucoside, delphinidin 3-(6-acetyl) glucoside, petunidin 3-(6-acetyl) glucoside, malvidin 3-(6-acetyl) glucoside and malvidin 3-O-glucoside concentrations were highest in Pinotage wines inoculated with T. delbrueckii. Cabernet franc wines inoculated with S. cerevisiae yeasts were highest in malvidin 3-(6-p-coumaroyl) glucoside, petunidin 3-(6-p-coumaroyl) glucoside, petunidin 3-O-glucoside, epicatechin gallate and epigallocatechin gallate concentrations. Total anthocyanins were highest in Pinotage (S. cerevisiae) wines and Cabernet franc (T. delbrueckii) wines. Flavanols were highest in Pinotage (T. delbrueckii) and Cabernet franc (S. cerevisiae) wines. It is evident from the results that yeast species has an impact on the flavonoid concentrations within a grape variety.